(untitled) (Applied Biological Research, 2023)
Melica grass has effective role in ecological landscape and its stability is affected by population genetics. Main purpose of this study was to investigate the relation and distance of Melica populations genetically that are grown in unlike topographic and climatic conditions. Karyotyping and leaf storage protein SDS PAGE were employed to investigate the genetic diversity of 10 populations of 2 species of Melica viz., M. persica and M. jacquemontii as major plants in ecological landscape of Esfahan, Alborz, Ghom, Golestan, Kerman and Yazd habitats in Iran. The result of karyotyping showed that all the populations have similar chromosomenumber(2n=2x=18), but cytogenetic parameters exhibited significant differences in all the populations. Ward similarity analysis revealed tions can be clustered into 4 groups. SDSPAGE of leaf protein indicated that the population of M. persica ‘21856’ had highest protein fragment while the lowest fragments belonged to M. jacquemontii [7683 and 10506]. Jaccard similarity coefficient revealed genetic variation in all the studied populations of M. persica, but M. jacquemontii showed no variation. M. persica had high diversity and more stability in ecological landscape and these results suggest that the species of M. jacquemontii is a subspecies of M. persica.